Mestiso 29 (NSIC Rc244H), A PhilRice-Bred three-line hybrid rice variety (Oryza sativa L.) for irrigated Lowland ecosystem. (2014)
The success of exploiting heterosis in rice as a key approach to curbing rice shortage by increasing domestic production necessitates the availability of adapted superior hybrids. This study aimed to evaluate the morpho-agronomic merits, grain yield potential, grain quality and reaction to biotic stress of Mestiso 29 (M29) against an inbred check (PSB Rc82) and a hybrid check (Mestiso 7). Hybrid variety development was done by crossing standard testers with assembled male parents in the source nursery. Progeny of the IR68897A x PR34302R cross exhibited positive heterosis in the testcross and re-testcross nurseries and was advanced for performance testing. The promising hybrid underwent a series of grain yield potential, pheno-typic acceptability and adaptability evaluations in multiple locations, for 7 seasons, with the designation PR36020H. Following the successful national testing and panel evaluation, PR36020H, developed by the hybrid rice breeding program of PhilRice, was released as NSIC Rc244H in 2011, locally known as Mestiso 29. M29 matured earlier than PSB Rc82 (110 DAS) was shorter than both checks (104 cm), recorded relatively high average grain yield at 7.03 at ha and attend maximum yield of 10 t ha-1. It demonstrated superiority over PSB Rc82 by 18.4% with season means and 27.1% during the wet season (WS), and gained positive yield advantage of 10.2% over Mestiso 7 during the WS. The grains are long (7.2 mm) and slender (2.1mm) with intermediate amylose content and other qualities comparable to that of PSB Rc82. M29 was softer and smoother than PSB Rc82 in cooked form but gained lower acceptability rating than Mestiso 7 by at least 20% in both raw and cooked form. It was susceptible to blast and sheath blight than both checks but more resistant to bacterial leaf blight than Mestiso 7. This variety was recommended for national cultivation in both dry and wet seasons, under the irrigated lowland ecosystem following transplanted culture, except for areas with incidence of bacterial leaf blight, blast and tungro.
Keywords: Rice -- Yield; Hybrid rice